Fabricating Aptamer-functionalized Ti3C2 therapeutic nanoplatform for targeted chemo-photothermal therapy of cancer. (February 2023) - Bai, Zhiqiang; Zhao, Lu; Feng, Haidi; Xu, Hui; Zhang, Nianping; Li, Yanjun; Song, Jinping; Bai, Yunfeng; Yang, Ronghua; Feng, Feng
Graphical abstract: A novel DOX/Ti3 C2 /Apt-M therapeutic nanoplatform was successfully fabricated, which could specifically target transmembrane glycoprotein mucin (MUC1) on the surface of MCF-7 tumor cells and display superior tumor suppressive ability through combination therapy. Highlights: Apt-functionalized Ti3 C2 therapeutic nanoplatform was successfully fabricated for the first time. The nanoplatform was used for targeted combined chemo-photothermal therapy of cancer. The therapeutic nanoplatform exhibited excellent active targeting performance, which was mediated by Apt-M. The therapeutic nanoplatform had effective antitumor effect in vitro and in vivo. Abstract: Aptamer (Apt) is a kind of recognition molecule with excellent affinity and high specificity. Transmembrane glycoprotein mucin (MUC1) is an important tumor biomarker overexpressed in MCF-7 tumor cells. MUC1 Apt (Apt-M) could specifically target MCF-7 tumor cells. Ti3 C2 nanosheets with high photothermal conversion efficiency were considered as a promising therapeutic nanoplatform for tumor therapy. Doxorubicin (DOX) is a common anti-tumor drug. Herein, a novel DOX/Ti3 C2 /Apt-M therapeutic nanoplatform was successfully fabricated, which could specifically target MCF-7 tumor cells. As expected, the temperature of DOX/Ti3 C2 /Apt-M therapeutic nanoplatform raised rapidly under laser irradiation. Meanwhile, chemotherapy was triggered through multimodal stimuli-responsive drug release from the DOX/Ti3 C2 /Apt-M therapeutic nanoplatform under acidic environment and laser-induced local high temperature. Encouragingly, the MCF-7 cell viability of DOX/Ti3 C2 /Apt-M with laser irradiation was only 26.9%. The tumor surface temperature of MCF-7 xenograft mice in the DOX/Ti3 C2 /Apt-M + Laser group rose to about 58.3 °C, which was significantly higher than other laser irradiation groups. The experiments in vitro and in vivo indicated that the DOX/Ti3 C2 /Apt-M therapeutic nanoplatform can rapidly accumulate in MCF-7 tumors with excellent active targeting properties, and display superior tumor suppressive ability through combination therapy. This work provides a new idea of targeted tumor therapy based on Ti3 C2 nanosheets.